Systematic Literature Review: Innovative Teaching Strategies For Integrating Entrepreneurship To Health Education - Sulistiawan, Andika; Idrus, Ali (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
ABSTRACT Background: Entrepreneurship has become an increasingly important skill in the healthcare industry, as healthcare professionals are being encouraged to think creatively and identify new opportunities for improvement. Objective: This study aims to explore innovative teaching strategies for integrating entrepreneurship into health education. Methods: A comprehensive literature review was conducted to identify existing teaching strategies that integrate entrepreneurship into health education. The data collection method used in this study is a systematic search of Scopus Database and reference lists following PRISMA flow chart guideline. Results: Several innovative teaching strategies were found, including case studies, simulation games, problem-based learning, and experiential learning. These strategies provide students with real-world scenarios and hands-on experiences, allowing them to develop their entrepreneurial skills in a healthcare context. Conclusion: By incorporating these innovative teaching strategies into health education, educators can equip future healthcare professionals with the knowledge and skills necessary to navigate the rapidly changing landscape of the healthcare industry and become successful entrepreneurs.